Processing of Aluminium-Silicon Alloy with Metal Carbide as Reinforcement through Powder-Based Additive Manufacturing: A Critical Study. (10th January 2022) - Raj Mohan, R.; Venkatraman, R.; Raghuraman, S.; Kumar, P. Manoj; Rinawa, Moti Lal; Subbiah, Ram; Arulmurugan, B.; Rajkumar, S.
Abstract : Powder-based additive manufacturing (PAM) is a potential fabrication approach in advancing state-of-the-art research to produce intricate components with high precision and accuracy in near-net form. In PAM, the raw materials are used in powder form, deposited on the surface layer by layer, and fused to produce the final product. PAM composite fabrication for biomedical implants, aircraft structure panels, and automotive brake rotary components is gaining popularity. In PAM composite fabrication, the aluminium cast alloy is widely preferred as a metal matrix for its unique properties, and different reinforcements are employed in the form of oxides, carbides, and nitrides. However, for enhancing the mechanical properties, the carbide form is predominantly considered. This comprehensive study focuses on contemporary research and reveals the effect of metal carbide's (MCs) addition to the aluminium matrix processed through various PAM processes, challenges involved, and potential scopes to advance the research.